2006
DOI: 10.1590/s0100-40422006000400044
|View full text |Cite
|
Sign up to set email alerts
|

A criação do curso de engenharia química na escola nacional de química da universidade do Brasil

Abstract: PERFIL DA QUÍMICA NO BRASIL NO INÍCIO DO SÉCULO XXDurante toda a época do Império e nas primeiras décadas do século XX, a Química figurou como uma atividade suplementar aos poucos laboratórios analíticos existentes ou como disciplina básica dos cursos de Medicina, Engenharia e, mais tarde, Farmá-cia. A tradição seguida nesses cursos baseou-se na orientação francesa, limitada a algumas poucas escolas profissionalizantes, que tinham como incumbência a formação dos elementos indispensá-veis ao funcionamento da so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
0
3
0
10
Order By: Relevance
“…71-79 / Junio 2021 Escuela Nacional de Química (ENQ) en 1933 por medio del decreto 23.016 del 28 de julio. La estructura del nuevo curso de Ingeniería Química fue aprobada en 1946 y la primera clase comenzó en 1952 (da Silva et al, 2006).…”
Section: Ingeniería Química En Latinoamericaunclassified
“…71-79 / Junio 2021 Escuela Nacional de Química (ENQ) en 1933 por medio del decreto 23.016 del 28 de julio. La estructura del nuevo curso de Ingeniería Química fue aprobada en 1946 y la primera clase comenzó en 1952 (da Silva et al, 2006).…”
Section: Ingeniería Química En Latinoamericaunclassified
“…Durante o império e nas primeiras décadas do século XX a Química estava como disciplina básica dos cursos de Medicina, Engenharia e Farmácia. O conhecimento químico era obtido através do aprendizado dos processos e das reações químicas envolvidas na preparação dos produtos fabricados na época (Silva, Santos & Afonso, 2006).…”
Section: Aprendizagem Significativa No Ensino Deunclassified
“…Cartilage is dense and load bearing, requiring a structural material such as chitosan to replace it. [218] Starch is also a viable choice for enzymatically degradable biomaterials. The degradation products of starch include glucose and its derivatives, all of which are biocompatible, making starch a favorable material.…”
Section: Intelligent Biomaterials For Tissue Engineering In Autoimmunmentioning
confidence: 99%
“…Starch is degraded naturally by the enzyme α-amylase, such that when starch is incorporated into a scaffold, α-amylase can be utilized to control the degradation rate. [218] Starch alone exhibits many properties suitable for different biomedical applications, such as cartilage tissue engineering, due to variations in structure [62] Collagen, which is biodegradable and biocompatible, can be added to numerous synthetic scaffolds to improve their biocompatibility as well as improve survivability of the transplanted cells. [219,220] In addition, a study investigating the efficacy of islet cell transplantation for reversing hyperglycemic conditions in rats induced with T1D using streptozotocin IV found that collagen IV was the most potent ECM component of the PLGA-based scaffold.…”
Section: Intelligent Biomaterials For Tissue Engineering In Autoimmunmentioning
confidence: 99%
See 1 more Smart Citation